2022
DOI: 10.1038/s41598-022-15682-w
|View full text |Cite
|
Sign up to set email alerts
|

Fabric muscle with a cooling acceleration structure for upper limb assistance soft exosuits

Abstract: Soft exosuits used for supporting human muscle strength must be lightweight and wearable. Shape memory alloy (SMA) spring-based fabric muscles (SFM) are light and flexible, making them suitable for soft and shape-conformable exosuits. However, SFMs have a slow actuation speed owing to the slow cooling rate of the SMA spring. This paper proposes a forced air-cooling fan-integrated fabric muscle (FCFM) that improves the cooling rate by arranging a thin-diameter SMA spring bundle with a high surface-area-to-volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Reproduced under the terms of the CC BY license. [ 101 ] Copyright 2022, The Authors, published by Springer Nature. d) Carlos III University of Madrid elbow SWRR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced under the terms of the CC BY license. [ 101 ] Copyright 2022, The Authors, published by Springer Nature. d) Carlos III University of Madrid elbow SWRR.…”
Section: Discussionmentioning
confidence: 99%
“…In most research in this area, the reported value was torque. Human Body [34,51,139,140] Skeletal muscle Human Body [34,46,[50][51][52]141] Skeletal muscle Step signal 1.55 Wearable assembly Korea Institute of Machinery and Materials [101] SMA (spring) Human Body [34,46,50,51,142] Skeletal However, for the hand, some devices have been developed to replicate/generate the force required for grasping and pinch activities. In the case of facial expressions, as with the finger joint, it is not measured on torque but the force that muscles generate in a direction to generate facial expressions.…”
Section: Joint Forces and Torquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research has been lacking on wearable robots that take comfort into consideration from the early stages of the development process. This has led to the development of soft and flexible suit-type wearable robots, wherein anchoring methods are utilized to stabilize the wearable robots on the body 4 , 5 . The anchoring methods can be classified based on the methods and materials used: elastic forces of stretchy fabrics 6 , stitching techniques 7 , webbing straps 8 , and hook and loop fasteners 9 .…”
Section: Introductionmentioning
confidence: 99%